2020
DOI: 10.3389/fpubh.2020.00220
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction for Non-alcoholic Fatty Liver Disease Based on Biochemical and Dietary Variables in a Chinese Han Population

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common liver disease globally, but there are no optimal methods for its prediction or diagnosis. The present cross-sectional study proposes a non-invasive tool for NAFLD screening. The study included 2,446 individuals, of whom 574 were NAFLD patients. Multivariable logistic regression analysis was used to identify risk factors for NAFLD and incorporate them in a risk prediction nomogram model; the variables included both clinical and lifestyle-related variables. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Likewise, the ability of the WHtR to identify the risk of NAFLD is supported by a number of studies (9, 10, 34). These two indices have been used as possible non-invasive tools for NAFLD screening (35). However, some studies have questioned these conclusions, arguing that height, the waist-to-hip ratio or the abdominal volume index are better predictors of NAFLD (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the ability of the WHtR to identify the risk of NAFLD is supported by a number of studies (9, 10, 34). These two indices have been used as possible non-invasive tools for NAFLD screening (35). However, some studies have questioned these conclusions, arguing that height, the waist-to-hip ratio or the abdominal volume index are better predictors of NAFLD (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, significantly weaker associations were detected in the people with DBP ≥ 90 mmHg, ALT < 40 U/L, FPG > 6.1 mmol/L, and HDL-c ≥ 1 mmol/L. Hypertension has been shown to be a risk factor for NAFLD ( 56 ), and HDL-c is negatively associated with the risk of NAFLD ( 76 ). Therefore, it is not surprising that the association of eGFR with NAFLD in the population with DBP ≥ 90 mmHg and HDL-c ≥ 1 mmol/L is weakened by the influence of DPB and HDL themselves on the risk of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Obese but metabolically healthy individuals have been shown to be at a greater risk of NAFLD progression than metabolically healthy individuals of a normal weight [ 28 ]. In addition, WC is a risk factor for NAFLD because it is associated with IR and hypertension [ 29 – 31 ]. An analysis of the characteristics of participants with differing fasting TG concentrations showed that BMI is higher in individuals with high fasting TG concentrations.…”
Section: Discussionmentioning
confidence: 99%